Potential role of weather, soil and plant microbial communities in rapid decline of apple trees - Singh, Jugpreet; Silva, Katchen Julliany Pereira; Fuchs, Marc; Khan, Awais (PloS one, 2019)
An unusual decline and collapse of young established trees known as "rapid apple decline" (RAD) has become a major concern for apple growers, particularly in the northeastern United States. This decline is characterized by stunted growth, pale yellow to reddish leaves, and tree collapse within weeks after onset of symptoms. We studied declining apple trees to identify potential involvement of abiotic and biotic stresses. We used 16S and ITS to profile bacterial and fungal communities in the soil, rhizosphere, roots, and shoots and tested for the presence of six viruses in scions and rootstocks of symptomatic and asymptomatic trees. The viruses detected were not associated with RAD symptoms. Bacterial and fungal populations were highly variable in plant tissue, soil and rhizosphere samples, with bacteroidetes, firmicutes, proteobacteria, acidobacteria, and actinobacteria the predominant bacterial classes in various samples. 'Alphaproteobacteria-rickettsiales', a bacterial class usually reduced in water-limiting soils, had significantly low abundance in root samples of symptomatic trees. Basidiomycota and Ascomycota fungal classes were the most common fungal classes observed, but neither showed differential enrichment between symptomatic and asymptomatic trees. Analyzing weather data showed an extremely cold winter followed by drought in 2015-2016, which likely weakened the trees to make them more susceptible to varied stresses. In addition, similar physical and nutritional soil composition from symptomatic and asymptomatic trees rules out the role of nutritional stress in RAD. Necrotic lesions and wood decay symptoms dispersing from bark or vascular cambium towards the heartwood were observed primarily below the graft union of declining apple trees, suggesting that the rootstock is the originating point of RAD. We speculate that differences in abiotic factors such as moisture levels in declining roots in combination with extreme weather profiles might cause RAD but cannot clearly rule out the involvement of other factors.